HUBUNGAN TINGKAT KEMATANGAN DAN SUHU DENGAN SISA MAKANAN LAUK NABATI PADA PASIEN ANAK DI RUANG INAP RUMKITAL DR. RAMELAN SURABAYA [Correlation between Cooked Level and Temperatures with Plate Waste of Vegetable Side Dish among Pediatric Patients at Naval Hospital Dr. Ramelan Surabaya] - Renata Saskia; Suzanna Primadona; Trias Mahmudiono (Universitas Airlangga, 2018)
Food evaluation in a hospital can be seen from patient’s plate waste. Plate waste can be infl uenced by patient's perception of the food served, such as appearance and taste. The aim of this study was to analyze the relationship of cooked level and temperature of vegetable side dishes with plate waste in the pediatric patient at naval hospital Dr. Ramelan Surabaya. The study was using cross sectional design. The sample of the study was thirty-two pediatric patient. The data collected through interview using a questionnaire and plate waste was observed by Comstock method. Chi-square was used to analyzed the correlation of cooked level and temperature of vegetable side dishes with plate waste. The results showed that there was a relationship between cooked level, the temperature of the vegetable side dish and plate waste which served on dinner time (p=0.049 and p=0.040), but there was no relationship between cooked level, the temperature of vegetable side dish and plate waste on lunch time (p=0.994 and p=0.505). There was a weak relationship between taste, aroma, portion with the patient's plate waste, due to the different appetite, eating habits and physiological conditions of the patients.